Preceramic Paper-Derived SiCf/SiCp Composites Obtained by Spark Plasma Sintering: Processing, Microstructure and Mechanical Properties; Materials; Vol. 13 iss. 3 - Li Ke; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich; Sedanova E. P. Elizaveta Pavlovna; Ivashutenko A. S. Alexander Sergeevich; Lider A. M. Andrey Markovich; Fan Ping; Yuan Daqing; Travitsky N. Nakhum (2020, 2020)
Title screen